UPLIFT AGE AND RATES OF THE GURVAN BOGD SYSTEM (GOBI-ALTAY) BY APATITE FISSION TRACK ANALYSIS - Vassallo R.; Jolivet M.; Ritz J.F.; Braucher R.; Larroque C.; Sue C.; Todbileg M.; Javkhlanbold D. (My University, 2007)
The dating of the uplift onset of the Mongolian mountain ranges, the northernmost relief associated with the India-Eurasia convergence, is a fundamental issue to better understand the mechanisms of propagation of the Cenozoic transpressive deformation in Central Asia. Using apatite fission tracks we determined the timing and strain rates of the tectonics affecting the Gurvan Bogd system, in the Gobi-Altay, since the Middle Mesozoic to the Late Cenozoic. The region was firstly affected by a Lower-Middle Jurassic tectonic phase, characterized by a vertical crustal movement larger than 2 km. Then followed a protracted period without major crustal vertical movements until the last uplift phase. The peneplanation of the Jurassic relief produced an erosional surface that has undergone negligible denudation or sedimentation for more than 100 Ma. This same surface corresponds to the present summit plateaux of the massifs, standing about 2000 m above the surrounding region, which corresponds to the vertical movement produced by the ongoing uplift. Modelling of fission track data from the massifs of Ih Bogd and Baga Bogd shows that this uplift phase probably started at 5 ± 3 Ma. The Gobi-Altay mountain range appears therefore as one of the youngest mountain ranges in Central Asia, which is consistent with the idea of a northward propagation of the transpressional deformation from the Himalayan front to the Siberian craton. The Cenozoic uplift rate of the massifs is estimated to be between 0.25 and 1 mm/yr, which is slightly higher than the upper Pleistocene vertical slip rates of the bordering faults. This suggests that thrust faults observed within the massifs would increase the uplift rate inside the massifs compared to the uplift rate determined at their boundaries. © 2007 Elsevier B.V. All rights reserved.
Keywords: CENTRAL ASIA; FISSION TRACKS; MASSIFS UPLIFT; MESOZOIC-CENOZOIC TECTONICS; MONGOLIA; SUMMIT PLATEAU; Jurassic; Pleistocene; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен